Ethnobotanical investigation of 'Chamaerops humilis' in the area of Beni Snous (Western of Algeria) - Medjati, Nadjat; Hasnaoui, Okkacha; Babali, Brahim; Hachemi, Noria (Mediterranean Botany, 2019)
The ethnobotanical potentials of Chamaerops humilis in the Béni Snous region (south-west of Tlemcen, western Algeria) has been studied to know the therapeutic utilities and the practices of the local populations, in order to valorize this resource. A series of ethnobotanical surveys were carried out using a questionnaire on the 3 municipalities of Beni Snous (Beni Bahdel, Azail, and Beni Snous). The frequency of use of Chamaerops humilis in the region of study is closely related to the profile of the investigated people. The results of this study reveal that Chamaerops humilis parts are used for therapeutic purposes by the local population: the heart of stipe as to treat dyspepsia (gastrointestinal attacks, 93.90%), fruits as an antiseptic (70.73%), roots for anemia (36.55%) and intestinal worms (30.10%), while the leaves are often used to treat diabetes (21.62%) and other gastrointestinal disorders (30.1%).